Facile synthesis of hierarchical dendrite-like structure iron layered double hydroxide nanohybrids for effective arsenic removal. Issue 80 (16th September 2016) - Tian, Na; Tian, Xike; Liu, Xiangwen; Zhou, Zhaoxin; Yang, Chao; Ma, Longlong; Tian, Chen; Li, Yong; Wang, Yanxin
Abstract : Stably hierarchical dendrite-like Fe-LDH/SEPs with excellent arsenic removal performance have been successfully developed. Abstract : The highly dispersed iron layered double hydroxide (Fe-LDH) nanoplates supported on sepiolite (SEP) nanofibers have been successfully prepared via in situ co-precipitation of an iron salt precursor. The as-obtained hierarchical dendrite-like Fe-LDH/SEPs possess high specific area, and exhibit excellent removal ability for arsenic, demonstrating promising potential in environment applications.